2018
DOI: 10.1161/strokeaha.118.021868
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging and Clinical Factors Associated With Ischemic Stroke in Patients Suspected of Cervical Artery Dissection

Abstract: Background and Purpose: Cervical artery dissection is a major cause of ischemic stroke in the young and presents with various imaging findings including stenosis and intramural hematoma (IMH). Our goal was to determine the relative contribution of lumen findings and IMH to acute ischemic stroke, and if a heavily T1-weighted sequence could more reliably detect IMH. Methods: IRB approval was obtained for this retrospective study of 254 patients undergoing MRI/MRA for suspected dissection. Imaging included stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Both CT angiography and MR angiography can effectively visualize vertebral artery dissection; however, CT angiography can be performed rapidly, and it allows simple reconstruction of the dissection artery in an acute setting . Recently, it was shown that using the heavily T1‐weighted sequence on MRI could increase the reliability of detection of intramural hematoma compared with using the T1‐fat saturation method, which could improve the accuracy of vertebral artery dissection diagnosis . In aortic dissection, multi‐detector row CT is the modality of choice for imaging acute aortic syndrome with a sensitivity and specificity approaching 100% …”
Section: Discussionmentioning
confidence: 99%
“…Both CT angiography and MR angiography can effectively visualize vertebral artery dissection; however, CT angiography can be performed rapidly, and it allows simple reconstruction of the dissection artery in an acute setting . Recently, it was shown that using the heavily T1‐weighted sequence on MRI could increase the reliability of detection of intramural hematoma compared with using the T1‐fat saturation method, which could improve the accuracy of vertebral artery dissection diagnosis . In aortic dissection, multi‐detector row CT is the modality of choice for imaging acute aortic syndrome with a sensitivity and specificity approaching 100% …”
Section: Discussionmentioning
confidence: 99%
“…The intimal flap and irregular surface of the vessel wall may reflect endothelial damage, which activates thrombus formation and may ultimately lead to occlusion or embolism [ 31 ]. Ischemic stroke in patients with CCAD is frequently associated with signs of thrombotic mechanisms observed upon imaging [ 6 , 32 ]. Coppenrath et al [ 33 ] demonstrated that intraluminal contrast enhancement on 2D-T1-weighted images revealed intraluminal thrombus formation and was strongly correlated with territorial ischemic stroke with an odds ratio of 32.0 (95% CI: 3.6-281) in 33 patients with spontaneous cervical artery dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Among the vascular risk factors, hypertension is most often present (26.7%-68.9%), as well as hyperlipidemia (17-51%) and smoking (12.8-52.0%), but less frequently diabetes (2.0-24.9%) and migraine (up to 21.2%) [1,41,50,51,54,57,58,[68][69][70][71]. Our findings are within this range, except hypertension, which was more frequent due to older age of our patients (Tables 1 and 4).…”
Section: Predisposing Factors and Causesmentioning
confidence: 99%
“…It manly comprises ischemic stroke (IS) of the brain or spinal cord, TIA, retinal infarcts, amaurosis fugax, and certain autonomic or cranial nerves [8,17,36,41,43,62,71,72,76,81,98,103,104]. IS of the brain is present in 30-64% of patients, either as a larger ischemic area or, rarely, as small lacunar lesions [36,69].…”
Section: Ischemia Occurrencementioning
confidence: 99%